Validation of the geriatric oral health assessment index (GOHAI) in the Malay language - Othman, W.N.W.; Muttalib, K.A.; Bakri, R.; Doss, J.G.; Jaafar, N.; Salleh, N.C.; Chen, S. (2006)
Objective: To translate and validate the Geriatric Oral Health Assessment Index (GOHAI into the Malay language for use in Malaysia. Methodology: The 6-Likert scale GOHAI was translated into the Malay language and self-administered on 189 subjects aged 60+. All subjects underwent oral status assessment. The measure was assessed for construct and discriminant validity, for test-retest reliability and principal component factor. Findings: Mean GOHAI score was 46.2 (SD 9.7, range 17-60). The Cronbach's alpha was 0.79. Mean GOHAI scores increased with more positive self-rated oral health and general health. The elderly with no perceived dental treatment need had higher mean GOHAI scores than those with perceived needs. There were slightly stronger inverse correlations between GOHAI scores and caries experience, number of teeth present, and number of pathologically mobile teeth. The measure demonstrated strong test-retest reliability. Eight of the 12 items had Spearman's r(3) 0.7. Only one principal factor was found at eigenvalue > 1. Using ANCOVA, self-rated perception of oral health and perceived need for dental treatment had the most significant impact on the GOHAI score. Conclusion and recommendations: The Malay language version of the GOHAI demonstrated acceptable validity and reliability and will be an important instrument to measure oral health-related quality of life among Malay-speaking Malaysians. Use of the Malay language version GOHAI should also be pursued among diverse adult age groups.